Pengaruh Kebijakan Utang, Ukuran Perusahaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Sri Hartanti Nuryatin; Leni Nur Pratiwi; Setiawan Setiawan; Rama Dhonal (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to identify and examine the factors that influence the company's value through the company's internal, including Company Policy, Debt Policy, and Company Size on Company Value in property and real estate listed on the Indonesian Sharia Stock Index (ISSI). This study uses a quantitative approach with secondary data, the number of samples is 10 companies that meet the research criteria using the purposive sampling method with annual financial reports for 2016-2020, so that 50 observational data are obtained. The data analysis technique used is panel data regression analysis with EViews version 9 analysis tool. The results of this study indicate that dividend policy does not affect firm value. Furthermore, debt policy has a significant effect in a positive direction on firm value. While the size of the company has a significant effect in a negative direction.